Fresh tissue parathyroid allotransplantation with short‐term immunosuppression: 1‐year follow‐up. Issue 11 (16th October 2017) - Yucesan, Emrah; Goncu, Beyza; Basoglu, Harun; Ozten Kandas, Nur; Ersoy, Yeliz Emine; Akbas, Fahri; Aysan, Erhan
Abstract: Background: Permanent hypoparathyroidism is a serious problem and requires medications indefinitely. Parathyroid allotransplantation (PA) with short‐term immunosuppression is definitive choice but long‐term results are not clear. Method: We performed PA from two donors to two recipients. Both recipients were 39‐year‐old females. Donors were a 32‐year‐old female and a 36‐year‐old male, who both have chronic kidney disease. Routine tests, viral markers, and cross‐matches were analyzed individually. The parathyroid glands were resected from the living donors, fragmented quickly in the operation room and injected into the left deltoid muscles of the two recipients. Results: Methylprednisolone was administered on post‐PA day one and two. Recipients were discharged from the hospital without complications. Calcium and PTH levels were observed throughout 1 year. We did not observe any complications during the follow‐up period. Medications ceased in post‐transplantation week 1 for Case 1 and after 1 month for Case 2. Conclusion: Fresh tissue PA with short‐term immunosuppression appears to be a promising technique that is easy to perform, is cost‐effective, has low risk of side effects and minimal complications with compatibility for HLA conditions. A longer follow‐up period and more case studies are needed to determine the risks and benefits of this procedure for future cases.